Bridging strategy versus buffering strategy: Enhancing crisis management capability in public management for relational and reputational improvement, and conflict avoidance - KIM, Soojin (Institutional Knowledge at Singapore Management University, 2017)
This study seeks to understand the effectiveness ofan organization’s communication strategy in enhancing its crisis managementcapability in public management. The relationships between two types ofcommunication strategies (bridging and buffering), crisis management capabilityin public management, relational improvement, reputational improvement, andconflict avoidance have been tested in this study to suggest how anorganization’s overall strategic orientation may help its ability to weather acrisis. A survey of communication managers was conducted in South Korea with 105responses, representing 105 organizations. Results revealed that organizations whichare predisposed toward adopting the bridging strategy as their maincommunication strategy are likely to report better crisis management capabilityin public management, and as a result they are likely to experience positive outcomesin their relationships with publics and in their reputation. Theoretical andpractical implications are discussed.